Scaling up agroforestry to achieve food security and environmental protection among smallholder farmers in Malawi - Beedy, Tracy; Ajayi, Oluyede C.; Sileshi, Gudeta W.; Kundhlande G; Chiundu G; Simons AJ (2012)
Malawi is a land-locked country in southern Africa. Three-fourths of Malawi’s 13 million people rely on smallholder agriculture for their livelihoods. Increasing population, accelerating deforestation, poor soil and water management, and increasing poverty and land degradation directly impact the food security and human health of millions of Malawians. Cropping systems which combine cereal crops, agroforestry and small doses of inorganic fertilizers produce food-crop yields greater than inorganic fertilizers alone on degraded soils, as well as recuperating soil nutrients over a period of years. These agroforestry practices improve the livelihoods of farm families, lower risks associated with fertilizer price increases and drought and at the same time improve biodiversity and nutrient and water cycling in the agro-ecosystem. The World Agroforestry Centre (ICRAF) has a long history of agroforestry research and development in Malawi dating back to the 1980s. In 2007-2011, ICRAF implemented the Malawi Agroforestry Food Security Project (AFSP) through financial support from Irish Aid. ICRAF’s task in AFSP was to build a strong partnership to reach 200,000 farming families in 11 districts. The purpose of AFSP was to combine tested agroforestry practices, effective partnership and informed policies to increase food security and income, and improve livelihood opportunities for rural communities in Malawi, through accelerated adoption of fertilizer trees, fruit trees, fodder trees and fuel-wood trees. To accomplish these purposes, ICRAF provided the farming communities with planting material (tree seeds and seedlings), and the knowledge of how to care for them and effectively combine them with food crops. The beneficiaries of the project saw increases in household food security and nutrition. However, difficulties were encountered in transporting tree seeds and seedlings across eleven districts in a timely fashion, and in managing the flow of reporting and disbursements of funding among such a large group of collaborators. Several solutions were implemented which improved performance in these areas, and which allowed the group to reach very near the targeted number of participants, and to plan for a second phase of the project.